Impact of tobacco advertisements on tobacco use among urban adolescents in India: results from a longitudinal study. Issue 3 (29th July 2011) - Arora, Monika; Gupta, Vinay K; Nazar, Gaurang P; Stigler, Melissa H; Perry, Cheryl L; Reddy, K Srinath
Abstract : Objectives: To examine the longitudinal relationship between exposure and receptivity to tobacco advertisements and progression towards tobacco use among adolescents in India. Design and setting: A 2-year longitudinal group-randomised trial, Mobilizing Youth for Tobacco Related Initiatives (MYTRI), was undertaken from 2004 to 2006 in 32 schools in Delhi and Chennai. Among the control schools (n=16), mixed-effects regression models were used to assess the objectives. Subjects: Students who were non-susceptible, never users of tobacco (n=2782) at baseline (2004) in the control schools of Project MYTRI, who progressed academically and were followed up at endline (2006). Main outcome measures: Progression towards tobacco use (on tobacco uptake continuum). Results: Bivariate results suggest that exposure to tobacco advertisements at baseline was associated in a dose-dependent manner with progression at endline. Students exposed at more than four places were 1.5 times (95% CI 1.12 to 1.94; p<0.05) more likely to progress towards tobacco use at endline versus those not exposed. Among boys, those exposed at more than four places were 1.7 times more likely to progress (95% CI 1.14 to 2.62; p<0.05). These significant results disappeared in multivariate analysis, when other psychosocial risk factors for tobacco use were controlled. In both bivariate and multivariate analyses, the risk of progression at endline was more than two times higher (95% CI 1.28 to 4.32; p<0.05) among boys who were highly receptive versus non-receptive boys. The same relationship did not hold among girls. Conclusion: High receptivity to tobacco advertising predicts future progression to tobacco use among boys in India. Suggestive evidence exists of a causal relationship between tobacco marketing and adolescent tobacco use.